Comparison of Microfluidic Synthesis of Silver Nanoparticles in Flow and Drop Reactors at Low Dean Numbers - Konstantia Nathanael; Nina M. Kovalchuk; Mark J. H. Simmons (Micromachines)
This study evaluates the performance of continuous flow and drop-based microfluidic devices for the synthesis of silver nanoparticles (AgNPs) under identical hydrodynamic and chemical conditions. Flows at low values of Dean number (De < 1) were investigated, where the contribution of the vortices forming inside the drop to the additional mixing inside the reactor should be most noticeable. In the drop-based microfluidic device, discrete aqueous drops serving as reactors were generated by flow focusing using silicone oil as the continuous phase. Aqueous solutions of reagents were supplied through two different channels merging just before the drops were formed. In the continuous flow device, the reagents merged at a Tee junction, and the reaction was carried out in the outlet tube. Although continuous flow systems may face challenges such as particle concentration reduction due to deposition on the channel wall or fouling, they are often more practical for research due to their operational simplicity, primarily through the elimination of the need to separate the aqueous nanoparticle dispersion from the oil phase. The results demonstrate that both microfluidic approaches produced AgNPs of similar sizes when the hydrodynamic conditions defined by the values of De and the residence time within the reactor were similar.